2022
DOI: 10.1080/00380237.2022.2066589
|View full text |Cite
|
Sign up to set email alerts
|

Performing Gender in Recreational Pole Dancing: Enabling and Constraining Factors

Abstract: She mainly works within the field of sport sociology and pedagogy but also has an interest in gender. Her current research project concerns the university education of and daily practice of physical education (PE) teachers regarding gymnastics as a subject area in high school PE in Denmark.Lone F. Thing is a professor and head of the Department of Sport and Social Sciences at the Norwegian School of Sport Sciences, Oslo, Norway. She has a master's degree (Cand. scient.) in the areas Humanities and Social Sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Men who pole violate heteromasculine norms by actively participating in pole dance. Prior research has found feminized spaces can be “safe spaces” for men to explore and understand gender and sexuality—even affording men opportunities to challenge them (Adams, 2011; Christofidou, 2018; Haltom, 2021; Jensen & Thing, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men who pole violate heteromasculine norms by actively participating in pole dance. Prior research has found feminized spaces can be “safe spaces” for men to explore and understand gender and sexuality—even affording men opportunities to challenge them (Adams, 2011; Christofidou, 2018; Haltom, 2021; Jensen & Thing, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, men in dance, cheerleading, figure skating, and baton twirling buy into a kind of masculinity that emphasizes strength‐based movements as opposed to women's lightness, timidity, and frailness (Adams, 2011; Grindstaff & West, 2006; Haltom, 2021; Haltom & Worthen, 2014). Pole dance is no different (Jensen & Thing, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that ironic communication is performative is based on the works of Judith Butler on gender (1988;[1990) and has informed such diverse studies of sport as exposing the performativity of statistics (Yarrow & Kranke, 2016), recreational pole dancing (Jensen & Thing, 2022), or enhancing our theoretical understanding of movement (Larsson & Quennerstedt, 2012). By adding a performative component to an idea of ironic representation, the approach relies on a process of repetition (Jackson, 2004;Larsson & Quennerstedt, 2012) termed 'stylized repetition of acts' (Butler, 2006(Butler, [1990.…”
Section: The Performativity Of Ironymentioning
confidence: 99%
“…During pole sports there is a proper load on all muscle groups: from the abdominal muscles and ending with biceps [3,6,7,8]. Considering the literary data of official sites, the practical activities of private clubs, academies and sports schools [9,10] it was found that the content of Pole Sport is the demonstration of the number on sports shells under the musical accompaniment. These numbers include elements that require those who are engaged in the development of strength, dynamic and static balance, flexibility.…”
Section: Introductionmentioning
confidence: 99%